Analisis Pengaruh Konten Promosi Media Sosial Instagram terhadap Persepsi Brand dan Niat Beli Konsumen: Studi Kasus Usaha Hijab Faril - Farah Ilaina; Shoimatul Fitria (Diponegoro Journal of Management, 2025)
The rapid development of social media has transformed how businesses interact with consumers, particularly in promotional activities. This study aims to analyse the influence of promotional content on Instagram on brand perception and purchase intention among consumers of Faril, a hijab business. A quantitative descriptive approach was used, with a survey method and questionnaires distributed to 100 respondents who follow and engage with Faril's Instagram account. The data were analysed using simple linear regression. The results indicate that Instagram promotional content has a positive and significant effect on both brand perception and purchase intention. The coefficient of determination (R²) shows that promotional content explains 61.1% of the variance in brand perception and 59.2% of the variance in purchase intention. These findings suggest that well-crafted Instagram content plays a crucial role in shaping consumers’ views and encouraging buying behaviour. The study highlights the importance of visual and engaging promotional strategies to strengthen brand image and drive consumer decisions in the hijab fashion industry. For small fashion businesses, Instagram is not just a communication platform but also a strategic tool for building trust, providing value, and connecting emotionally with the target audience. The research contributes to the growing body of knowledge on the effectiveness of social media marketing and offers practical insights for entrepreneurs and digital marketers seeking to optimise their online promotional efforts.